2012
DOI: 10.1088/0953-8984/24/4/046002
|View full text |Cite
|
Sign up to set email alerts
|

Extended scaling in the magnetic critical phenomenology of the σ-phase Fe0.53–Cr0.47and Fe0.52–V0.48alloys

Abstract: The magnetization of the sigma-phase Fe(0.53)Cr(0.47) and Fe(0.52)V(0.48) alloys was studied as a function of temperature and field. The experiments show that both materials behave magnetically as re-entrant spin glass systems. Field versus temperature diagrams were obtained where the locations of the paramagnetic phase, the intermediate ferromagnetic-like phase and the spin glass fundamental state were displayed. These diagrams are in qualitative agreement with the predictions of the mean field theory for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
1
24
1
Order By: Relevance
“…1. These values are slightly smaller than the value of 1.6 found previously for -FeV with x=48 and T C = 42 [25]. The values of T irr were defined as temperature of bifurcation in the Mcurves.…”
mentioning
confidence: 76%
“…1. These values are slightly smaller than the value of 1.6 found previously for -FeV with x=48 and T C = 42 [25]. The values of T irr were defined as temperature of bifurcation in the Mcurves.…”
mentioning
confidence: 76%
“…in all four cases the ground state is constituted by a spin glass (SG) which in the case of the Fe-Cr and Fe-V systems has a re-entrant character [11]. Some magnetic features revealed for  in the Fe-Re [9] and Fe-Mo systems [11,12] indicate that it also may be the case here. It is known that non-linear AC susceptibilities, 2, 3,…, can give a valuable information on the character of magnetism.…”
Section: Introductionmentioning
confidence: 68%
“…This finding is in line with our previous observations concerning the magnetism in other -phase binary alloys viz. Fe-Cr, Fe-V and Fe-Re [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Its magnetism was, however, lately shown to be more complex than initially anticipated viz. in both cases it has a re-entrant character [9]. Furthermore, nuclear magnetic resonance measurements performed on r-FeV samples revealed that vanadium atoms present on all five sub lattices were magnetic [10].…”
Section: Introductionmentioning
confidence: 92%